Harnessing the full potential of an ageing population. (Research'eu results magazine)
Europe's population is rapidly ageing. To help societies and economies adapt to this demographic reality, the EU-funded MOPACT project has explored new and innovative policies that will turn Europe's longevity revolution into a major asset for the continent's future social and economic development.